SCIENCE OF STRENGTH TRAINING UNDERSTAND THE ANATOMY AND PHYSIOLOGY TO TRANSFORM YOUR BODY - Current, Austin (Dorling Kindersley Limited, 2021)
Whether you want to tone and sculpt, lose weight, gain a sporting edge, or support mobility, strength training will help achieve your goals. This book reveals the mechanics of each movement in detail, identifying the muscles and joint actions working below the surface, so you can maximize your workouts and feel you're getting it right. With flexible training programmes and a myth-busting look at the science behind building muscles, this book will strengthen both body and mind.